Reply to comment by E. Martin, M. Martin, and O. Sigmarsson on "Continental geochemical signatures in dacites from Iceland and implications for models of early Archaean crust formation" by M. Willbold, E. Hegner, A. Stracke, and A. Rocholl - Willbold, Matthias; Hegner, Ernst; Stracke, Andreas; Rocholl, Alexander (Earth and Planetary Science Letters, 2010)
ISSN:0012-821X ISSN:1385-013X